The Paradox of Redistribution and Strategies of Equality: Welfare State Institutions, Inequality and Poverty in the Western Countries - Walter Korpi; Joakim Palme (Luxembourg Income Study (LIS), 1998)
The debates on how to reduce poverty and inequality have focused on two controversial questions. One is whether social policies should be targeted to low- income groups or universal; another whether benefits should be equal for all or earnings-related. Traditional arguments in favor of targeting and flat-rate benefits, focusing on the distribution of the money actually transferred, have neglected three policy-relevant considerations: 1. The size of redistributive budgets is not fixed but reflects the structure of welfare state institutions. 2. there tends to be a tradeoff between the degree of low-income targeting and the size of redistributive budgets. 3. Outcomes of market-based distribution are often even more unequal than those of earnings-related social insurance programs. We argue that social insurance institutions are of central importance for redistributive outcomes. using new data bases, our comparative analyses of the effects of different institutional types of welfare states on poverty and inequality indicate that institutional differences lead to unexpected outcomes and generate the paradox of redistribution: The more we target benefits at the poor and the more concerned we are with creating equality via equal public transfers to all, the less likely we are to reduce poverty and inequality.
Keywords: 330; Einkommensumverteilung; Wirtschaftliche Effizienz; Sozialstaat; Europa